2020
DOI: 10.1136/bmjopen-2020-038411
|View full text |Cite
|
Sign up to set email alerts
|

SAFE, a new therapeutic intervention for families of children with autism: a randomised controlled feasibility trial

Abstract: ObjectivesTo establish the feasibility of a definitive randomised controlled trial of Systemic Autism-related Family Enabling (SAFE), an intervention for families of children with autism.DesignA randomised, controlled, multicentred feasibility study.SettingParticipants were identified from three National Health Service (NHS) diagnosing centres in Plymouth and Cornwall and a community pathway.Participants34 families of a child with a diagnosis of autism severity level 1 or 2 between 3 and 16 years. Four familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Using multiple cases allows for comparison and the analysis of differences, and to refine theory by examining its ability to make sense of new contexts. The data is drawn from a larger study of an intervention for families with children who have a diagnosis of autism (McKenzie et al, 2020). Parents were interviewed using the Parent Development Interview (PDI: Aber et al, 1985), a semi-structured interview asking parents about their child, their relationship with their child and their experience of being parented.…”
Section: Methodsmentioning
confidence: 99%
“…Using multiple cases allows for comparison and the analysis of differences, and to refine theory by examining its ability to make sense of new contexts. The data is drawn from a larger study of an intervention for families with children who have a diagnosis of autism (McKenzie et al, 2020). Parents were interviewed using the Parent Development Interview (PDI: Aber et al, 1985), a semi-structured interview asking parents about their child, their relationship with their child and their experience of being parented.…”
Section: Methodsmentioning
confidence: 99%
“…Although family support is necessary, it is likely that this should be provided for all families soon after receiving a diagnosis rather than needing to make a later referral for FT. An early FT intervention that could be offered to ASD families is Systemic Autism-related Family Enabling (SAFE), which was developed by McKenzie et al (2020) using the evidence-based principles of FT that have been reported to be effective in improving outcomes across a range of conditions (Carr, 2018;Stratton, 2005Stratton, , 2016 and focusses on improving family communication to enhance family mental wellbeing. There is evidence from a pilot randomised controlled trial to show that providing a group of families with five sessions of SAFE within 12 months after receiving a diagnosis significantly improved parent-rated family functioning compared with a group of controls (McKenzie et al, 2020). This suggests that families could benefit from a FT intervention soon after receiving the young person's ASD diagnosis, and if this is not provided, families may be referred to FT at a later point to receive support.…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Coming to terms with and managing an ASD diagnosis can put a strain on young people and their families. It is clear from research that family members of young people with autism often experience higher levels of stress, anxiety and depressive symptoms than that of non-clinical populations, with 50% of parents presenting a comorbid mental health problem (McKenzie et al, 2020;Spain et al, 2017). Previous research has also revealed that maternal exposure to trauma and abuse can increase the risk of their offspring developing ASD, which indicates that mental health problems may already be high in this parent group irrespective of their child's autism (Roberts et al, 2014(Roberts et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that parents of children with autism are at appreciable risk of poor mental health, and unsatisfactory service interactions exacerbate their problems 7. Mothers of children with autism report lower levels of satisfaction with service interactions than those of children with other disabilities, and parents are more likely to be hospitalised for mental disorders than those of neurotypical children 7.…”
Section: Lauren Wallace-thompson Communications and Content Manager Ideas Alliancementioning
confidence: 99%
“…Evidence shows that parents of children with autism are at appreciable risk of poor mental health, and unsatisfactory service interactions exacerbate their problems 7. Mothers of children with autism report lower levels of satisfaction with service interactions than those of children with other disabilities, and parents are more likely to be hospitalised for mental disorders than those of neurotypical children 7. Bromley is a borough in the South East of England with over 330 000 residents, and the experience for families here has been similar to that of thousands of families across the UK: long waiting times for diagnosis and specialist services, parents battling over scarce resources and support, and stretched budgets.…”
Section: Lauren Wallace-thompson Communications and Content Manager Ideas Alliancementioning
confidence: 99%